OPTIMIZING HEMOGLOBIN LEVELS IN ANEMIC ADOLESCENT GIRLS: A COMPARATIVE STUDY OF GREEN BEAN AND RED BEAN PORRIDGE SUPPLEMENTATION - Ayuk Naimah Naimah; Rani Fitriani (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2024)
Anemia is a serious health problem in Indonesia, with a prevalence rate reaching 23.7%, higher in females compared to males. The prevalence of anemia in females even reached 27.2% in 2018, while in males it was 20.3%. Nutrient contents such as vitamin A, calcium, and potassium in green and red beans are believed to increase hemoglobin levels in the body. Therefore, this study aims to evaluate the effectiveness of providing green and red bean porridge in increasing hemoglobin levels in adolescent girls suffering from anemia at SMK PUSPA BANGSA BANYUWANGI. In this study, a quasi-experimental design with the randomized pre-test-post-test control group design approach was used. Out of 40 respondents receiving treatment, 20 respondents were given green bean porridge and 20 respondents were given red bean porridge, each with a dose of 200cc for 14 days. The results of the analysis showed that both types of porridge were effective in increasing hemoglobin levels in adolescent girls with anemia, as evidenced by the Paired T-Test with a P value of 0.000, which is smaller than α (0.05). Thus, it can be concluded that green and red bean porridge can be an effective alternative to increase hemoglobin levels in anemic adolescent girls at SMK PUSPA BANGSA BANYUWANGI.